National Survey of Youth in Custody, 2008-2009 ([Verlag nicht ermittelbar], 2013)
The National Survey of Youth in Custody (NSYC) is part of the BJS National Prison Rape Statistics Program to gather mandated data on the incidence of prevalence of sexual assault in juvenile facilities under the Prison Rape Elimination Act of 2003 (PREA; P.L. 108-79). The Act requires a 10 percent sample of juvenile facilities to be listed by incidence of sexual assault. Data are collected directly from youth in a private setting using audio computer-assisted self interview (ACASI) technology with a touch-screen laptop and an audio feed to maximize inmate confidentiality and minimize literacy issues. The first year of collection includes nearly 200 juvenile facilities, with an estimated 10,000 completed interviews with youth. The NSYC utilized two questionnaires, based on the age of the respondent. The Older Youth questionnaire was administered to youths ages 15 and older, and the Younger Youth questionnaire was administered to those 14 and younger. The survey was divided into five sections. Section A collected background information, such as details of admission to facility and demographics including education, height, weight, race, ethnicity, gender, sexual orientation, and history of any forced sexual contact. Section B, Facility Perceptions and Victimization, included respondents' opinions of the facility and staff, any incidence of gang activity, and any injuries that had occurred. Section C, Sexual Activity Within Facility, captured the types of sexual contact that occurred and the circumstances of sexual contact. Section D, Description of Events with Youth, and Section E, Description of Events with Staff Member, focused on when and where the contact occurred, the race and gender of the other youths or staff members, if threats or coersion were involved, and outcomes, included whether or not the sexual contact was reported. Other variables include debriefing questions about respondents' experiences completing the survey, interviewer observations, created variables to summarize victimization reports (due to the complicated routing in Section C), weight and stratification data, and administrative data about the facilities.